2015
DOI: 10.2147/tcrm.s83776
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of peripherally inserted central catheter-related infection among cancer patients

Abstract: BackgroundAs the use of peripherally inserted central catheters (PICCs) increased in chemotherapy, the identification of complications and risk factors became essential to prevent patient harm. But little is known about PICC-related infection and risk factors among patients with cancer. Our study was to identify the prevalence, patterns, and risk factors of catheter-related infections associated with PICCs.MethodsA 3-year prospective cohort study was conducted in a university-affiliated hospital. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 24 publications
3
35
2
Order By: Relevance
“…86 Peripherally inserted central catheters (PICC) are commonly employed in cancer patients and in 2 cohorts the incidence of PICC-related BSIs was very low (0.05 per 1000 catheter days), although the incidence of localized PICC-associated infections and thrombosis was high. 87,88 Although CVC is associated with an increased risk of BSI, in neutropenic patients most of the infections are caused by translocation of intestinal bacteria. It has been estimated that approximately 40-50% of bloodstream infections in oncologic settings are due to mucosal barrier injury.…”
Section: Central Venous Cathetersmentioning
confidence: 99%
“…86 Peripherally inserted central catheters (PICC) are commonly employed in cancer patients and in 2 cohorts the incidence of PICC-related BSIs was very low (0.05 per 1000 catheter days), although the incidence of localized PICC-associated infections and thrombosis was high. 87,88 Although CVC is associated with an increased risk of BSI, in neutropenic patients most of the infections are caused by translocation of intestinal bacteria. It has been estimated that approximately 40-50% of bloodstream infections in oncologic settings are due to mucosal barrier injury.…”
Section: Central Venous Cathetersmentioning
confidence: 99%
“…Peripherally inserted central catheters (PICCs) play a fundamental role in intravenous therapy and treatment. PICCs have a wide range of applicability in different patients, including paediatric and elderly patients, patients with chronic or acute diseases, patients undergoing surgery or chemotherapy and patients who need parenteral nutrition and medication, such as antibiotics and fluids 1–4…”
Section: Introductionmentioning
confidence: 99%
“…reported that multi-lumens and power PICC could increase the risk of PICC-related bloodstream infection 12 . A study based on cancer patients demonstrated that fixing method, indwelling season, catheter care, and tip position were significantly associated with incidence of PICC-related bloodstream infection 13 . Nevertheless, there was no consistent conclusion.…”
Section: Introductionmentioning
confidence: 99%